Implementasi Pop Up Book sebagai Media Interaktif untuk Meningkatkan Minat Belajar Fikih Siswa MI Kelas 1 pada Materi Salat Fardhu - Zulaikhah, Arina; Labib, Ahmad (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
This research is motivated by the low interest of students in learning Islamic jurisprudence, especially the material on obligatory prayers in grade 1 of MI NU 51 Bendosari. This study aims to determine the implementation of Pop Up Book media in increasing learning interest, identifying student responses, and its impact on material understanding. The method used is descriptive qualitative with data collection techniques through observation, interviews, documentation, and questionnaires. Data analysis is carried out through reduction, presentation, and drawing conclusions. The results show that the implementation of Pop Up Book media is carried out through the planning, implementation, and evaluation stages that actively involve students. Student interest in learning has increased significantly, indicated by increased attention, curiosity, participation, and positive attitudes in learning. In addition, understanding of the material on obligatory prayers has also increased. The use of Pop Up Books has been proven to be able to change Islamic jurisprudence learning from being initially considered abstract to being more concrete, interesting, and enjoyable. The active involvement of students in exploring the media content supports increased concentration and curiosity. Recommendations for teachers to use Pop Up Book media as a variation in fiqh learning so that students are more interested and can easily understand abstract material and teachers should combine Pop Up Book with demonstration methods or direct practice so that learning is more meaningful.